LA PREVENTION SECONDAIRE DE L’ADDICTION AU TABAC CHEZ LES ADOLESCENTS EN MILIEU SCOLAIRE AU LYCEE CHIEKH ELHADED D’AMIZOURBEJAIA (ALGERIE) - Wahiba, Hatem (European Scientific Journal, ESJ, 2014)
Addiction to psycho-active substances in general, and to tobacco in particular constitutes a serious problem of public health due to which it is important to elaborate and execute effective programs in their preventive purpose. The purpose of this work is to evaluate the effectiveness of a psycho-social program of prevention against tobacco to teenagers in school medium in Cheikh Elhaded High School of Amizour – Béjaia (Algeria). The results have proved the effectiveness of the preventive program where the study has shown differences statistically significant between the results of the previous test and the following test: these results are not due to hazard but to the preventive program proposed by the searcher. The research hypotheses have been confirmed.